High Speed Data Compression Method of Merge Unit Based on SCD File - Chen, Xingtian; Xiong, Xiaofu; Bai, Yong; Hu, Haiyang (Ji suan ji ke xue, 2023)
In modern smart grid, many merging units are installed in smart substation to release transient data of current transformer and voltage transformer synchronously, these transient data need to be saved for several years, so as to cover the life cycle of equipment and provide original information support for condition maintenance and reliability of equipment, but such long-time and high-frequency massive data is a difficult problem for storage equipment.In this paper, the high-frequency transient data are preprocessed in three forms: fixed, state-changing and periodic-changing.Tthe fixed part is replaced by merge's APPID in SCD file, the state-changing part is replaced by event record file, and the periodic-changing part is represented by two-channel diffe-rence and periodic difference in SCD file, and the final compression coding is completed with 16-bit Huffman.The final test shows that the compression ratio of this compression method is larger than that of common hardware compression card, and the compressio